Sexual Harassment di Tempat Kerja dalam Perspektif Kriminologi - Fadillah, Astuti Nur (Bacarita Law Journal, 2022)
This study aims to be able to analyze the problem of sexual harassment in the workplace from a criminological perspective. The method used is normative juridical research. Criminology is a study that looks at the causes of a crime, as well as how the efforts and efforts to overcome the crime. One of the sad forms of crime that occurs in society is Sexual harassment or what we know as sexual harassment. Sexual harassment can happen anywhere, without exception in the workplace. One form of sexual harassment is “Quid pro quo” (this is for that). Causes of Evil behavior can arise due to social, political, and many other things. The causes of sexual harassment in the workplace are power relations, gender inequality, perpetrators do not get the consequences of their actions